Recent development of unmanned aerial vehicle for plant protection in East Asia - Xiongkui, He; Bonds, Jane; Herbst, Andreas; Langenakens, Jan (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Recently, the growing use of unmanned aerial vehicles (UAV) for pesticide application has been reported against a wide range of crops with promising results in East Asian countries such as Japan, South Korea and China. This UAV-based application technology for agrochemicals is considered as a high efficiency alternative to the conventional manual spray operations and a low-cost choice as compared to the classical manned aerial application. However, the technology adoption rate and the designed optimal sprayer suitable for drone application for small scale farm remains at the development stage in China and also in Japan. This paper reports the current status of drone pesticide application in China and makes comparisons with its neighbor countries Japan and South Korea in terms of different UAV platforms and their implementation in plant protection for different crops. Challenges and opportunities for future development of UAV-based pesticide application technology are also discussed.Keywords: plant protection, UAV pesticide application, RPA spray technology, spray quality, flight control, agrochemical applicationDOI: 10.3965/j.ijabe.20171003.3248Citation: He X K, Bonds J, Herbst A, Langenakens J. Recent development of unmanned aerial vehicle for plant protection in East Asia. Int J Agric & Biol Eng, 2017; 10(3): 18–30.